Biodefense challenges - Schmaljohn, Connie (Henry Stewart Talks, 2007)
Viruses as bioterrorism or biowarfare threats, Smallpox virus and monkeypox virus, Equine encephalitis viruses: Venezuelan, eastern and western equine encephalitis viruses, Ebola and Marburg viruses, Rift Valley fever virus, Genetically engineered viruses
Archived at 2018/08/22